Development of an objective water security index and assessment of its association with quality of life in urban areas of developing countries. (December 2018) - Shrestha, Sadhana; Aihara, Yoko; Bhattarai, Arun P.; Bista, Niranjan; Kondo, Naoki; Futaba, Kazama; Nishida, Kei; Shindo, Junko
Abstract: A composite metric assessing water security's physical dimension at the micro/ community level is lacking but is essential for setting priorities for program and policy implementations. We prepared an objective index (OI) of water security to measure the physical dimension using a model centered on household water-use behavior in developing countries' urban areas. A cross-sectional household survey (n = 1500) with multi-stage cluster design was conducted from December 2015 to February 2016 in the Kathmandu Valley, which has faced long-term, severe water shortage. A structured questionnaire probed socio-demographic characteristics, water sources, frequency and quantity of water use, cost related to water, etc. A 15-item water insecurity scale was used to measure subjective and experiential dimension of water insecurity. The World Health Organization Quality of Life – BREF was used to measure quality of life (QoL). The QoL has been considered as proxy of well-being in this study. The OI measured differential water security within small cities, the utility's service areas for instance, and identified area-specific key dimensions that need improvement. Overall, the OI and its key dimensions can be useful measures to design water-scarcity averting programs and policies, specific to a particular community's needs. The increased OI values were significantly and positively associated with better physical and psychological health and better social relationship domains of QoL suggesting health implications of water security. Highlights: A composite water security metric focused on micro level and physical dimension is rare. The proposed objective index is centred on household water-use behaviour. The proposed objective index is based on quantifiable indicators. The objective index was useful in measuring differential water security within cities. Water security was significantly associated with well-being of people.